Perancangan Sistem Single Sign-On (SSO) Berbasis QR Code pada PT.XYZ dengan Pendekatan Model Waterfall untuk Lingkungan Korporasi - Nugroho, Agung Prasetyo; David, Felix (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Hundreds of systems at PT. XYZ cause problems in managing credentials, as each user is required to remember multiple credentials. This study developed a QR Code-based Single Sign-On (SSO) system to simplify the login process using the Waterfall model Software Development Life Cycle (SDLC) approach. The login process is completed by scanning a QR Code that represents the user's authentication token, and the login status is synchronized in real-time using WebSocket. The scope of this study is limited to the development of a login page prototype and testing login time and QR scanning time, compared with other methods. This study does not include penetration testing or cryptography. The results from black-box testing show that all features function properly, and User Acceptance Testing (UAT) achieved an average score of 90.4%. Therefore, this QR Code-based SSO login system has proven to be effective, secure, and suitable for use as a modern authentication solution.
Keywords: Single Sign-On; Autentikasi; QR Code; WebSocket; Passwordless; Token